Employing personality-rich virtual persons: new tools required - Iurgel, Ido A. (2011)
Digital personalities are virtual characters that possess situation dependent, personality revealing behaviors. This paper introduces concepts, current and prospective usages of personality-rich virtual characters, and focus on authoring issues for artists that want to create digital portrays of digital persons. Different categories of digital personalities are introduced, in particular virtual actors for CG-movies are explained in more detail because of the importance of understanding the functioning of virtual actors—other types of virtual personalities will often be build upon the faculties of virtual actors. It is proposed that an essential feature of the prospective authoring process of digital personalities is the support of generalization. This would allow for a “concrete authoring”, that modifies and defines concrete cases. Thus, the author would be able to employ concrete cases as basis for generalizations. In this context, possible technologies that would support a concrete authoring process are presented, in particular Case-Based Reasoning.